Penerapan Model Discovery Learning Untuk Meningkatkan Prestasi Belajar Siswa di Sekolah Menengah Atas: Application of the Discovery Learning Model to Improve Student Achievement in High School - Imron, Muhammad (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study was to determine the effect of the Discovery Learning model in improving student achievement.This research method uses classroom action research methods, then this research was conducted in 2 cycles, where the first cycle uses discovery learning method that is equipped with structured work drawings on the topic of wall construction material and basic ship construction and in the second cycle uses discovery learning method which is equipped with a simulator model on the topic of basic shipbuilding construction with ship wall construction. The results showed the number of students who reached the Minimum Mastery Criteria increased from the first cycle to the second cycle, from 15 students (46.87%) to 27 students (84.37%). This increase also occurred in the increase in student activity, where julmah students were active in the first cycle 37.50% of students to 90.62% of students. So that these results indicate an indication of increased student understanding of ship interior work material.